2022
DOI: 10.1037/dev0001415
|View full text |Cite
|
Sign up to set email alerts
|

How does inhibitory control predict emotion regulation in preschool? The role of individual children’s interactions with teachers and peers.

Abstract: Emotion regulation is foundational to children's psychological wellbeing and future school adjustment. As young children are spending increasing amounts of time in preschool programs, investigating how early childhood classrooms can foster emotion regulation development is warranted. In this study, we tested individual children's interactions with teachers and peers as potential mechanisms through which inhibitory control supports emotion regulation in the preschool classroom. Participants included 767 prescho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 103 publications
0
2
0
1
Order By: Relevance
“…In line with this notion, it has been shown that better IC is associated with better resilience to potential interruptions 18 , 19 , with better control over emotional reactivity 20 , and with memory suppression following trauma 21 . In addition, resilience following childhood adversity was associated with enhanced inhibitory control abilities over task-irrelevant negative information 10 , and impairments in inhibitory control during emotional tasks was suggested to increase the risk for depression 13 , 22 .…”
Section: Introductionmentioning
confidence: 71%
“…In line with this notion, it has been shown that better IC is associated with better resilience to potential interruptions 18 , 19 , with better control over emotional reactivity 20 , and with memory suppression following trauma 21 . In addition, resilience following childhood adversity was associated with enhanced inhibitory control abilities over task-irrelevant negative information 10 , and impairments in inhibitory control during emotional tasks was suggested to increase the risk for depression 13 , 22 .…”
Section: Introductionmentioning
confidence: 71%
“…In the early years parent-child, as well as, peer interactions provide opportunities to observe and extract models of appropriate behaviours and participate in conversational exchanges (Jung & Short, 2002). Furthermore, parents modulate children's behaviour and help them to regulate their emotions (Alamos et al, 2022). The behavioural regulation aspects of EF are thus functioning before typically developing hearing children reach 6 years old and in deaf children with deaf parents.…”
Section: Discussionmentioning
confidence: 99%
“…Es así como el presente trabajo tiene el objetivo de evaluar el impacto de una intervención grupal realizada en el ámbito escolar, basada en mindfulness, sobre la atención sostenida, la atención selectiva y el control inhibitorio en alumnos de 9 a 11 años. Motiva la decisión de analizar el impacto sobre el control inhibitorio, por sobre otras funciones ejecutivas, en primer lugar, por el rol esencial en el desarrollo infantil del control inhibitorio, ya que está estrechamente relacionado con la capacidad de los niños para regular su comportamiento, resistir impulsos y tomar decisiones reflexivas (Alamos et al, 2022, Carlson & Wang, 2007, Fino et al, 2014. Y en segundo lugar, dado que la intervención se basa en mindfulness, que implica la conciencia y regulación de los procesos mentales, el control inhibitorio es particularmente pertinente, ya que está relacionado con la capacidad de regular respuestas automáticas y dirigir la atención de manera consciente (Bedard et al, 2002;Neill et al, 1995;Veer et al, 2017).…”
unclassified